Certeza, duda escéptica y saber - Samuel M. Cabanchick (Crítica)
Traditionally, the skeptic has been considered as a threat to our claims to true and justified knowledge. Also, certainty appears to be as the highest possible degree of knowledge. Knowledge and certainty are thus opposed to skepticism. This paper wants to show that 'certainty' and knowledge are, probably, incompatible notions, and that the possibility of a doubt about the assumed certainty is a necessary condition to distinguish between belief and knowledge, and to construe any kind of knowledge. Its starting point is Moore's notion of cerfainty, Moore demands that the expression of certainty (and, consequently, its formalization) should assume certain basic intuitions. One of them is the non-transmissibility of certainty; another intuition, fundamental to its Proof of the Existence of the World, is that certainty should be implied by knowledge. The claim of certainty: